Wsp-based analysis of Wolbachia strains associated with Phlebotomus papatasi and P. sergenti (Diptera: Psychodidae) main cutaneous leishmaniasis vectors, introduction of a new subgroup wSerg. (3rd April 2018) - Karimian, Fateh; Vatandoost, Hassan; Rassi, Yavar; Maleki-Ravasan, Naseh; Choubdar, Nayyereh; Koosha, Mona; Arzamani, Kourosh; Moradi-Asl, Eslam; Veysi, Arshad; Alipour, Hamzeh; Shirani, Manouchehr; Oshaghi, Mohammad Ali
Abstract: Sand flies of Phlebotomus papatasi and P. sergenti are the main vectors of cutaneous leishmanisis (CL) in the old world. We aimed to screen Iranian P. papatasi and P. sergenti for their natural infections with Wolbachia and to determine their phylogenetic association with other species. Wolbachia surface protein (wsp) gene was PCR amplified from DNA extracted from Phlebotomus species, sequenced, and were analysed in combination with wsp sequences related to Phelebtominae and other insects. All Wolbachia -infecting Iranian sand flies of P. papatasi and P. sergenti were classified in the Supergroup A., Wolbachia isolated from P. sergenti were clustered in a new subgroup within Supergroup A so-called wSreg. The Wolbachia strains identified from the P. papatasi clustered mainly in the subgroup wPap and partly in wSerg. Multiple Wholbachia infection within a single population of P.papatasi warrants investigation on existence and intensity of cytoplasmic incompatibility between the wPap and wSerg subgroups.